HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN TENDANGAN LURUS ATLET PENCAK SILAT STARLAK KUINTAL STROPEDO DANAU BINGKUANG - Esiska Yanirma; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: based on the background that created and with the phenomena exists, then the research can be formulated as follows: If there is a power relationship of limb muscles with the ability to kick straight STARLAK pencak silat athletes KUINTAL STROPEDO (SKS) Lake Bingkuang, in accordance with the issues raised above, the purpose of this research is to know the power relationship with limb muscles ability kicks straight athletes pencak silat STARLAK KUINTAL STROPEDO (SKS) Lake Bingkuang. Data that has been collected and then analyzed. That becomes the variable X is power and limb muscles that become variable Y is the ability to kick straight. As for the hypothesis to be tested,